An Analysis of Expressive Speech Acts in Comments on Lex Fridman’s Podcast with Elon Musk - Amelia Nur'aini; Siti Zuhriah Ariatmi (Universitas Veteran Bangun Nusantara, 2025)
This research analyzes expressive speech acts the viral YouTube podcast episode “Elon Musk: Neuralink and the Future of Humanity | Lex Fridman Podcast #438,” which drew massive attention and engagement from global audiences. Employing a descriptive qualitative method, the study identifies sixteen types of expressive speech acts based on the frameworks of Norrick (1978), Austin (1962), and Vanderveken & Kubo (2002), and examines their communicative functions using Leech’s (1983) taxonomy. The data were collected through web scraping and restricted to English-language comments posted between August and October 2024. The analysis reveals that thanking, greetings, and attitudes are the most frequently used expressive types, with most serving convivial and collaborative functions. These findings highlight how digital platforms like YouTube facilitate public emotional engagement with technological discourse. The study contributes to pragmatic research by offering insights into how netizens express psychological and emotional responses in digital communication, especially in reaction to controversial innovations such as Neuralink.